2011
DOI: 10.1007/s11906-011-0201-3
|View full text |Cite
|
Sign up to set email alerts
|

Does Blood Pressure Variability Modulate Cardiovascular Risk?

Abstract: Exactly how hypertension causes end organ damage and vascular events is poorly understood. Yet the concept that underlying "usual" blood pressure (BP) accounts for all BP-related risk of vascular events and for the benefits of BP-lowering drugs has come to underpin clinical guidelines on the diagnosis and treatment of hypertension. This article reviews evidence that variability in BP also predicts risk of stroke and other vascular events independently of mean BP and evidence that drug-class effects on variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 98 publications
2
50
0
Order By: Relevance
“…However, the clinical significance of BP variability in cardiovascular diseases remains controversial. [14][15][16] Determinants and prognostic relevance for cardiovascular outcomes are probably different among short-term (beat-to-beat), short-term (for 24 hours), midterm (day-to-day), and long-term BP variability (visit-to-visit).…”
Section: Day-by-day Bp Variability and Stroke Outcome 1833mentioning
confidence: 99%
“…However, the clinical significance of BP variability in cardiovascular diseases remains controversial. [14][15][16] Determinants and prognostic relevance for cardiovascular outcomes are probably different among short-term (beat-to-beat), short-term (for 24 hours), midterm (day-to-day), and long-term BP variability (visit-to-visit).…”
Section: Day-by-day Bp Variability and Stroke Outcome 1833mentioning
confidence: 99%
“…In addition, BPV also seems to contribute in the development of microvascular complications in type 1 and type 2 diabetes and with the progression of renal failure and mortality in patients at end-stage chronic kidney disease. Therefore, increased BPV is nowadays considered a new risk factor of cardiovascular disease and a possible new target for antihypertensive therapy [6,64,[93][94][95][96].…”
Section: Perspectivesmentioning
confidence: 99%
“…However, ambulatory blood pressure measurement (ABPM) provides serial BP measurements and information on different subsets of BP, like day-and night time BP, resulting in a high reproducibility and the possibility to evaluate circadian distribution of BP levels, respectively [11,12]. It could be shown that by the use of ABPM, treatment evaluations in clinical trials as well as in clinical practice become more efficient and reliable [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%